KAJIAN ASPEK HUKUM INTERNASIONAL PADA KASUS TUMPAHAN MINYAK KAPAL TANKER EXXON VALDES - Zulfaidah Ariany (TEKNIK, 2011)
The ships operation can occur a lot of possibilities accidents which caused a fatal accident, affect to the damagethe cargo and crew, and also on the environment that may affect to the industry and coastal beaches, and thecontinuity of living things around it. This paper tried to make the consideration that always vigilant andanticipated the occurrence of ships accidents at seas. Tanker Vessel Exxon Valdes cause huge losses in history,so the author interested to discuss in the light of international legal studies. At the end of this paper we’ll belearned the engaged the shipping and their best frame works, the society, and the nation, especially for the State